Virus attacks! / Dianne Cheong Lee Mei - Cheong, Dianne Lee Mei (Universiti Teknologi MARA Cawangan Pahang, 1989)
You don't have to be doing anything wrong to get hit. But you can spread it unwittingly while carrying out your legitimate business, that is computing. It makes its presence on a floppy disk. Then it installs itself in the computer's RAM. Hence, the computer is bugged! Rogue programs or sets of instructions that can secretly be spread among computers are known as viruses and they are disruptive software. They caused growing alarm among computer users. Viruses got their name because the mimic in the computer world the behavior of biological viruses. Viruses can travel either over a computer network or on an infected disk passed by hand between computer users. Once the infection has spread, the virus might do something as benign as displaying a simple message on a computer screen or as destructive as erasing the data on an entire disk. Pirate software and games package are viewed as a major source of viruses. So do watch out for computer diskettes from unknown sources! Public domain systems like bulletin boards also are susceptible to virus infection. Unsuspecting individuals PC users can innocently download an infected program, lend the contaminated floppy disks to others and the cycle starts. Booting from a carrier diskette would result in creating a vicious cycle of infection. Vandals and mischief makers, often known as hackers, who write viruses are usually brilliant low-level programmers who find it a challenge cracking complicated computer codes. The approach which they usually take involves one of the two approaches. Either the use of a 'trapdoor' in a program or of a 'logic' bomb. A trapdoor is a deliberate break in the course of a program. Using this gap the criminal can then insert additional instructions which may totally disrupt the system. The logic bomb is triggered either by some combination of events in the system, for example a particular individual signing on to the system, or by a given date and time being reached. The bomb then obliterates all the stored data or otherwise destroys the files. There are many strains of viruses. Some are malicious and some are not. Microcomputer users in Thailand are facing widespread infections from the so-called 'Israeli' virus. Several computer vendors admitted that they had found that several of their PCs with the 'Israeli' virus which is spread after it attaches itself to an executable program and then that program is run in another microcomputer. The virus then installs itself in the computer's RAM and any subsequent files that are executed becomes infected. Each time an infected program is run, it increases' in size by just over 1.8kb and in time the computer begins to slow down or the program becomes too large to be run. This computer virus is also known as the 'Friday the 13th virus' since the virus deleted files on October 13,1989.